Precarity among care workers in Honduras - Sabillón Casco, Josué (2025)
This study highlight the precarity of care workers in Honduras using data from the Permanent Household Survey for Multiple  Purposes (EPHPM) in September 2022. It examines the socioeconomic conditions and work environment, social protection, and wages. The results reveal that care workers face completely precarious conditions, with low wages, unstable working hours, and a lack of access to social protection. It is important to recognize care work as a fundamental activity for improving working conditions and ensure comprehensive well-being.